ASUPAN KALSIUM DAN VITAMIN D PADA ANAK INDONESIA USIA 2 – 12 TAHUN [Calcium and Vitamin D Intake of Indonesian Children 2-12 Years Old] - Victoria Valentina; Nurheni Sri Palupi; Nuri Andarwulan (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
ASUPAN KALSIUM DAN VITAMIN D PADA ANAK INDONESIA USIA 2 – 12 TAHUN[Calcium and Vitamin D Intake of Indonesian Children 2-12 Years Old]Victoria Valentina*, Nurheni Sri Palupi dan Nuri AndarwulanDepartemen Ilmu dan Teknologi Pangan, Fakultas Teknologi Pertanian, Institut Pertanian Bogor, Bogor Diterima 18 Januari 2014 / Disetujui 25 Juni 2014ABSTRACT Food consumption is playing an important role for nutritional status of children 2-12 years old. During growth and development phase, body needs macro and micro nutrients even more than later phase. The process can not be catched up at later stage therefore it is very important to pay attention to food consumption during this phase. This study used secondary data of South East Asian Nutrition Surveys (SEANUTS) 2011-2012 which was covered recapitulation profile data of 300 children age 2-12 years old representative of 48 districts in Indonesia. The study showed that Indonesian children consuming less calcium and vitamin D-rich foods than the recommended daily allowance (RDA). It does not reflects on the result of anthropometry data, vitamin D on the blood and bone mass density since the dietary recall 24 hours shows only food consumption in that specific day while nutritional status shows a result of longer process. However, vitamin D in blood has a significant correlation with bone mass density of tibia bone (p<0.05). Deficiency of calcium and mainly vitamin D is a new finding at this time. Therefore, the study showed that fortification of calcium and vitamin min D in food become important to improve nutritional status of Indonesian children. 20% of RDA per serving size twice a day is recommended as well for fortification level of Calcium and Vitamin D.